A Field Study to Assess Physical Activity Levels During Weekdays Among Students in the First Cycle and its Relationship with Lower Limb Muscle Strength - Al-Hadabi, Badriya; El-Ashkar, Heba; Sassi, Radhouane (Journal of Physical Education, 2024)
This study aimed to assess physical activity levels during 3 school days among first cycle students and its relationship with lower limb muscle strength. Twenty-eight students from the Governor of Muscat were participated in this study, (age: 11.8±0.3 years, height: 9.0±148 cm, mass Body: 14.5±34.8 kg, BMI: 5.3±19.2 kg.m-2 To assess physical activity levels, the ActiGraph GT3X device was used for 3 school days during the week (from 8:00 am to 12:00 pm, daily). All participating performed two tests of lower limb muscle strength (CMJ - FCM). Study results showed that the average physical activity levels of students during 3 school days were (455.9± 56.7minutes) and (26.3±6.6 minutes) for both sedentary physical behavior (SPA) and high-intensity physical activity (VPA), respectively. The results also revealed that the level of moderate and vigorous physical activity level (MVPA) during 3 days of school reached (67.9 ±17.01minutes), which is approximately (22.6 minutes per day), meaning that there was a noticeable decrease in the levels of physical activity practiced during school days (3 days). per week for first cycle students. The results also showed that there was no relationship between all physical activity levels (SPA, LPA, MPA, VPA, MVPA) and lower limb muscle strength tests (CMJ - FCM) among the students (0.05<p).